Trade and the Firm-Internal Allocation of Workers to Tasks - Michael Koch; Hartmut Egger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper looks inside the firm and investigates how trade alters the matching of worker-specific abilities and task-specific requirements. The outcome of this matching depends on how firms organize their recruitment process and how much they invest into the screening of applicants. In the open economy, the most productive firms start exporting. They increase their market share and therefore find it attractive to increase their screening investment, which improves the matching outcome. Things are different for non-exporters, whose market share shrinks in the open economy, lowering their incentive to invest to screen applicants. Due to this asymmetric response, access to trade raises the dispersion of labor productivity between heterogeneous producers, while at the same time increasing the average quality of worker-task matches and thus economy-wide labor productivity. The productivity-enhancing effect of endogenous adjustments in the firm-internal allocation of workers to tasks points to a so far unexplored channel through which gains from trade can materialize.
Keywords: F12; F16; L23; 330